2017
DOI: 10.1111/jdv.14098
|View full text |Cite
|
Sign up to set email alerts
|

Filaggrin gene mutations and the distribution of filaggrin in oral mucosa of patients with oral lichen planus and healthy controls

Abstract: OLP/OLL is associated with an altered distribution of filaggrin in the oral mucosa independently of defects in the FLG. Patients with OLP/OLL did not display more active dermatoses other than cutaneous LP when compared to healthy controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…ProFLG is detectable in human non‐keratinized, parakeratinized and orthokeratinized oral epithelium, although FLG monomer is expressed in only the orthokeratinized palate . Expression of FLG proteins in the human oral mucosa was shown to increase markedly under pathological conditions involving hyperkeratosis such as lichen planus and leukoplakia, which occur independently of defects in the FLG gene . These data suggest that the enzymatic breakdown of proFLG and the resulting pattern of stratification are likely to be distinct among stratified tissues such as the skin and oral mucosa.…”
Section: Introductionmentioning
confidence: 99%
“…ProFLG is detectable in human non‐keratinized, parakeratinized and orthokeratinized oral epithelium, although FLG monomer is expressed in only the orthokeratinized palate . Expression of FLG proteins in the human oral mucosa was shown to increase markedly under pathological conditions involving hyperkeratosis such as lichen planus and leukoplakia, which occur independently of defects in the FLG gene . These data suggest that the enzymatic breakdown of proFLG and the resulting pattern of stratification are likely to be distinct among stratified tissues such as the skin and oral mucosa.…”
Section: Introductionmentioning
confidence: 99%
“…As for SPRR1B, it was shown that its expression is up-regulated in OSCC-derived stem cells, in addition to having a role in the growth and proliferation of these cells by regulating RASSF4, a tumor suppressor gene related with the MAPK pathway, 20 suggesting that the overexpression of SPRR1B may be related to the carcinogenesis of OSCC, as well as the maintenance of stem cells of this carcinoma (Michifuri et al, 2013). Filaggrin, coded by the FLG gene, is a protein located in the stratum corneum of the skin, contributing to its integrity and strength (McGrath and Uitto, 2008), and patients with OLP have an altered distribution and overexpression of this protein in the oral mucosa (Larsen et al, 2017). Though filaggrin may be involved in lesions in the oral mucosa (Itoiz et al, 1985), further investigations are needed to show the role of this protein and the malignancy potential of OLP.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Larsen et al 8 reported in this edition of the JEADV set out to test several hypotheses relating to the relationship between oral lichenoid lesions (OLL, including oral LP), filaggrin expression, FLG mutations and co-associated skin conditions. Thirty-eight patients with OLL (including 19 with oral LP) and 11 with non-specific stomatitis were compared with 29 unaffected controls.…”
mentioning
confidence: 99%
“…The study by Larsen et al . reported in this edition of the JEADV set out to test several hypotheses relating to the relationship between oral lichenoid lesions (OLL, including oral LP), filaggrin expression, FLG mutations and co‐associated skin conditions.…”
mentioning
confidence: 99%